The effect of sugar, starch and pectin as microbial energy sources on in vitro forage fermentation kinetics - Malan, Marcia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2009.